(untitled) (Eurasian Journal of Engineering and Technology, 2023)
Thus, the basic measurement schemes of the light current receiving devices of optoelectronic converters studied above show that the measurement scheme of a photodiode with a negative bias voltage has several advantages and ensures stable operation of the circuit, that is, a secondary converter-operation that converts the photodiode current into a voltage characteristic of its output circuit amplifier circuit is included. It can be seen from the diagram that the double filtering of the output signal increases the accuracy of the photoelectric characteristics of the photodiode measuring circuit to a high level.